2013
DOI: 10.1364/oe.21.013840
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal mode selectivity by frequency conversion in second-order nonlinear optical waveguides

Abstract: Abstract:We explore theoretically the feasibility of using frequency conversion by sum-or difference-frequency generation, enabled by threewave-mixing, for selectively multiplexing orthogonal input waveforms that overlap in time and frequency. Such a process would enable a drop device for use in a transparent optical network using temporally orthogonal waveforms to encode different channels. We model the process using coupled-mode equations appropriate for wave mixing in a uniform secondorder nonlinear optical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(118 citation statements)
references
References 29 publications
5
113
0
Order By: Relevance
“…The GF kernels found here are similar in form to those earlier presented for FWM BS [15,16], and to those for three-wave mixing [6], apart from the exponential phase terms which are seen to be linear in both the input and output times. We adopt the notation that β r and β s are to be measured relative to the average group slowness β av = (β r + β s ) /2, such that they obey β r = −β s > 0.…”
Section: Theory Of Asymmetrically-pumped Bragg Scatteringsupporting
confidence: 81%
See 3 more Smart Citations
“…The GF kernels found here are similar in form to those earlier presented for FWM BS [15,16], and to those for three-wave mixing [6], apart from the exponential phase terms which are seen to be linear in both the input and output times. We adopt the notation that β r and β s are to be measured relative to the average group slowness β av = (β r + β s ) /2, such that they obey β r = −β s > 0.…”
Section: Theory Of Asymmetrically-pumped Bragg Scatteringsupporting
confidence: 81%
“…In the present case where a p is of constant amplitude, the Heaviside functions never vanish as allowed by BS using two pulsed pumps in a full collision [15,17]. However, as for three-wave mixing [6], by increasing ζ their influence can be diminished asymptotically.…”
Section: Theory Of Asymmetrically-pumped Bragg Scatteringmentioning
confidence: 69%
See 2 more Smart Citations
“…In fact, the conventional traveling-wave Raman protocol [21,47] is nearly single-mode [53], but the mode selectivity degrades at high efficiency -a phenomenon encountered also in engineering mode-selective frequency conversion [54]. Recently Reddy et al showed how to achieve high mode selectivity and high efficiency in frequency conversion by double-passing or multi-passing the active medium, so that each interaction was weak enough to remain effectively single-mode [55,56]. The perfect mode-selectivity of the cavity memory analysed here can be understood as the multi-pass limit of this approach, where the interaction describing a single pass through the cavity is weak, and therefore separable, whereas the coherent combination of all cavity round-trips provides for arbitrarily high efficiency while retaining temporal mode selectivity.…”
Section: Mode Selectivitymentioning
confidence: 99%